Potentiating Effect of Adrenaline on Adenosine Diphosphate - Induced Reduction in Rabbit Circulating Platelet Count: Inhibition by Dihydroergotoxine - Holmes, Ian B (Thrombosis and Haemostasis, 1979)
The number of circulating platelets was monitored in anaesthetized rabbits by a contiuous flow technique, using a Technicon Autocounter®. Transient reductions in circulating platelet count induced by a submaximal dose of adenosine diphosphate (ADP) were potentiated by concomitant infusion of adrenaline at doses (1-25 μg/kg i.v.) which did not influence platelet count when infused alone. The adrenaline effect was dose-dependent. Repeated infusions of adrenaline at 15 min intervals resulted in reproducible reductions in circulating platelet count during an observation period of at least 105 min.Dihydroergotoxine (DHET), administered either i.v. (2.5 - 10 μg/kg) or intraduodenally (i.d.; 25 - 100 μg/kg), inhibited adrenaline-induced potentiation dose-dependently; ADP- induced effects were not influenced. Duration of action was relatively long, and significant inhibitory activity was still apparent 50 (i.v.) and 115 (i.d.) min after drug administration.DHET doses inhibiting adrenaline-induced potentiation of platelet aggregation in the rabbit are similar to doses used in the treatment of impaired human cerebral function. It is conceivable that DHET could prevent activitation of human platelets by catecholamines released into the blood stream in clinical stress situations.